INTRODUCTION TO THE SPECIAL ISSUE ABOUT RETURN MIGRATION - Barcevičius, Egidijus (Politologija, 2015)
During the last two decades, Lithuania has experienced a high rate of labour migration, which peaked during the early years of EU membership (2004–2006) and once again during the recent economic and financial crisis (2009–2011). This has had some far-reaching economic and social effects, including a significant decrease of labour supply, brain waste, and further deterioration of the demographic balance. Yet a significant number of migrants do return back into the labour market of Lithuania, albeit with different levels of success. While there has been an extensive amount of research on migration and mobility of Lithuanians, very few studies have addressed the question of how the former migrants actually perform upon coming back. This is the key question for the papers presented in this volume. The research in this volume benefited from the support of the Lithuanian Science Council to the project “Friends or Foes: The Integration of Return Migrants into the Labour Market and Society of Lithuania” which was implemented in March 2013 – March 2015. The researchers carried out six surveys as well as more than 70 interviews. The key research questions were: how important are professional motives for the decision to come back to Lithuania; do the skills and knowledge gained abroad help to get a job and advance career in Lithuania; do the employers and the society at large value the work experience from abroad; and is the secondary education system prepared to accommodate school pupils who lived and studied in foreign countries? This rest of this volume consists of four articles. The text by Egidijus Barcevičius and Vaida Gineikytė finds that professional motives do matter as a reason for return of highly qualified persons. In general, they do not experience too many difficulties to find employment in Lithuania, although individual experiences do vary a lot, and the public sector (universities) often struggles to accommodate returning researchers. Dovilė Žvalionytė focusses on all the returnees most of whom were not highly qualified according to the definition used in the previous article. She finds that Lithuanian labour market is not very receptive to the experience of labour migrants because of information asymmetry. According to her, many employers (and the society at large) consider return as a signal of failure and, given that verifying the actual experience of returnees is difficult, the mobility experience tends to be disregarded or even considered as a disadvantage. Irma Budginaitė and Rūta Mašidlauskaitė in their article argue that although the Lithuanian education system does have formal tools to help the children of returning migrants, these tools are rarely used, especially in smaller towns. This means that individual schools and teachers have to improvise and while some approach the returning children with support and compassion, there are cases where teachers’ lack relevant skills and schools fail to create the right atmosphere for return. Finally, Vaida Gineikytė analyses Lithuanians working in the European Commission (EC) who are obviously not return migrants but do take an active part in various diasporic networks and maintain rather close personal links with Lithuania. The article finds that many of these officials have informal contacts with the Lithuanian public service, not least because many of them have worked previously in the national public sector and thus the friends and professional networks are somewhat overlapping. There is some evidence of these officials advising the national institutions, formally and informally, although keeping strictly to the confidentiality and ethical standards expected from the EU officials. However, sometimes the national institutions themselves fail to ask for advice, although this could both save time and help to formulate more informed negotiating positions.